Pre-operative Embolization Facilitating the Surgical Resection of Retroperitoneal Paraganglioma Associated to Horseshoe Kidney - Abdou, A.; Almaghraoui, O.; Moufid, K.; Alaoui, M. (Cardiology and Cardiovascular Medicine, 2020)
The authors report the successful removal of a paraganglioma associated with horseshoe kidney after preoperative embolization and two previous failed surgical attempts undergone in another center. Complete excision of the tumour was performed smoothly. Total blood loss was 205 ml and the surg-ical time was approximately 160 minutes. The posto-per-ative period was uneventful. Histological findings were of paraganglioma, and there was no surgical margin. This case emphasizes the necessity to include preoperative embolization in the manage-ment of difficult or inextirpable retro-peritoneal para-ganglioma and should be considered in difficult case.